2018
DOI: 10.1177/0271678x18765828
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine rapidly replenishes central nervous system glutathione measured via magnetic resonance spectroscopy in human neonates with hypoxic-ischemic encephalopathy

Abstract: Persistent oxidative stress depletes reduced glutathione (GSH), an intracellular antioxidant and an important determinant of CNS injury after hypoxia ischemia. We used standard, short echo time Stimulated Echo Acquisition Mode (STEAM) to detect GSH by magnetic resonance spectroscopy (MRS) in 24 term neonates with hypoxic-ischemic encephalopathy (HIE), on day of life 5-6, after rewarming from therapeutic hypothermia. MRS demonstrated reliable, consistent GSH of 1·64 ± 0·20 mM in the basal ganglia immediately be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…Furthermore, NAC has been investigated as a safe neuroprotectant in animal models and human neonates with hypoxic ischemic injury, infection, and white matter injury. 22,34,37,38 In addition, we have demonstrated that NAC can significantly increase [GSH] in the basal ganglia of neonates 5 days after hypoxic ischemic birth, mitigating ongoing oxidative stress. 34 Cerebral oxidative stress has been well described during acute opioid withdrawal.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Furthermore, NAC has been investigated as a safe neuroprotectant in animal models and human neonates with hypoxic ischemic injury, infection, and white matter injury. 22,34,37,38 In addition, we have demonstrated that NAC can significantly increase [GSH] in the basal ganglia of neonates 5 days after hypoxic ischemic birth, mitigating ongoing oxidative stress. 34 Cerebral oxidative stress has been well described during acute opioid withdrawal.…”
Section: Discussionmentioning
confidence: 81%
“…Phantom solutions (0.5-5 mM GSH, 5 mM DTT, 10 mM Choline, 25 mM Creatine, phosphate-buffered saline, pH 7.1) were used to validate [GSH], [Cr], and [Cho] quantification by MRS, using the water peak as a standard. 34 Quantification of GSH and Cr in phantoms by LCModel processing with our specialized basis set showed excellent correlation with known concentrations of these metabolites. 34 The phantom solution standard curves for [GSH], [Cho], and [Cr] are shown in Fig.…”
Section: Mrs Data Processingmentioning
confidence: 82%
See 3 more Smart Citations